The Amygdala Network for Processing Itch in Human Brains - Hideki Mochizuki; Loren Hernandez; Gil Yosipovitch; Norihiro Sadato; Ryusuke Kakigi (Medical Journals Sweden, 2020)
Itch is an unpleasant and aversive somatosensory experience. These negative emotions significantly affect mental health in patients with chronic itch; it is therefore important to understand the brain mechanism of negative emotions due to itch. The amygdala is a key hub of networks regulating negative emotions due to itch. However, the exact network involved in this process is unknown. This study used functional magnetic resonance imaging to investigate the amygdala network processing itch in 25 healthy subjects. Brain activity was measured during electrical itch stimuli using functional magnetic resonance imaging. During itch stimuli the amygdala exhibited increased functional connectivity with key brain regions of the serotonergic system responsible for negative emotions (the medial habenula and the median raphe nucleus) and with the memory system, which is responsible for consolidating emotional experiences (the parahippocampus and perirhinal cortex). The serotonergic and memory systems may become therapeutic targets to prevent or reduce diminished mental health commonly seen in chronic itch patients.